Pengembangan Infrastruktur Penunjang Aktivitas Nelayan di Lappa Kecamatan Sinjai Utara - Nurainun Magfirah; Muhammad Yamin Jinca; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
Lappa Village in North Sinjai District, Sinjai Regency, has the potential to empower fisheries and marine natural products. However, its potential in the utilization business is not optimal. Some of the problems encountered, one of which is the infrastructure that supports fishing community activities has not been realized properly and has not been optimally carried out, the level of environmental quality and the level of welfare is still low. This study aims to find out how the level of availability of supporting infrastructure for fishing activities is based on standards and propose a strategy for developing fisherman environmental infrastructure in an effort to improve the economy of small fishing communities in Lappa Village, North Sinjai District. The data used are primary and secondary data obtained from literature studies, observations and interviews. Data analysis techniques are literature synthesis analysis, qualitative descriptive analysis, Likert scale analysis, infrastructure service level analysis, and SWOT analysis. The results showed that the availability of supporting facilities for fishermen's activities in Lappa Village was 63.6% with the medium category and infrastructure for supporting fishing activities still needs to be done better pier planning and road widening, as well as meeting the needs for utility infrastructure (electricity and clean water).